Factors influencing the choices of infant feeding of HIV-positive mothers in southern Ghana: the role of counsellors, mothers, families and socio-economic status - Laar, Alexander Suuk (Health Economics Unit, 2023)
This study assessed the perspectives of HIV-positive mothers and family members (i.e., grandmothers and fathers) of infant feeding options for HIV-positive mothers in southern Ghana. This entailed individual interviews with 40 HIV-positive mothers with infants, and 6 focus group discussions with HIV-positive mothers, fathers and grandmothers of unknown status in two urban districts. All infants born to the HIV-positive mothers in both districts had been breastfed. Breastfeeding was initiated any time between three hours and three days following birth. While some of the infants had been exclusively breast-fed, none had been exclusively replacement fed. Early mixed feeding patterns are deeply entrenched and the adoption of either EBF or ERF or both, represents departures from the social norms. Barriers to replacement feeding by HIV-positive mothers' included cultural and familial influences, socio-economic factors (including cost of infant formula, and lack of access to resources (for example, fridges, clean water, fuel and others) which are necessary for the safe preparation and storage of formula milk and fear over stigma and discrimination. Interventions designed to promote safer infant feeding among HIV-infected mothers in these settings need to be mindful of these barriers (socio-economic, cultural and familial) that these women face. Failure by policy makers to incorporate these issues will continue to lead to a gap between well-intended policies and programmes, and actual practices of HIV-positive mothers.